The Influence Of Location And Service Quality On Purchasing Decisions For Electrical Appliances At Paci Electrical Store In Palembang - Sari, Ellyza Putri Arum; Naruliza, Esty; Ermelia, Sri (Jurnal Fokus Manajemen, 2025)
The objective of this study is to determine how location and service quality, both partially and simultaneously, influence consumer purchasing decisions for electrical equipment at Toko Listrik Paci Palembang. In this research, a sample of 250 respondents was selected to illustrate how consumers make purchasing decisions. Data were obtained from 250 individuals who completed the survey. The results show that the location variable (X1) has a significant effect on purchasing decisions (Y), with a significance value of 0.020 (less than 0.050), indicating that H0 is rejected and H1 is accepted. The service quality variable (X2) also has a significant influence, with a significance value of 0.000 (≤ 0.050), suggesting that service quality plays a crucial role in influencing consumer purchasing decisions. Location also shows a significant effect with a constant value of -0.105, indicating that service quality significantly contributes to consumer decision-making, supported by the significance value of 0.020. Being located in a market environment with numerous competing stores may reduce consumer purchasing decisions due to the abundance of alternatives. Customers' decisions to purchase electrical tools at Toko Listrik Paci Palembang are partially and simultaneously influenced by store location and the level of service provided. However, further research should consider additional elements that may affect customer choices.